A method for preparing high-density silver tin oxide electrical contact material
Through high vacuum high-temperature sintering and high-temperature repression processes, the thermal decomposition reaction of CuO is used to eliminate closed pores inside the Ag-SnO2 electrical contact material, solving the problem of low density of materials prepared by powder metallurgy, and achieving material preparation with high density and excellent electrical contact performance.
Patent Information
- Application Number
- CN202310065251.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-01-17
AI Technical Summary
There is a problem of low density inside the Ag-SnO2 electrical contact materials prepared by the existing powder metallurgy method, resulting in limited electrical contact performance.
High vacuum high-temperature sintering and high-temperature repression processes are adopted to eliminate closed pores inside the material through the thermal decomposition reaction of CuO, and pressure-keeping treatment is carried out under high vacuum conditions to improve the density of the material.
Effectively eliminate residual pores inside electrical contact materials, improve the density and electrical contact performance of the material, and realize the preparation of fully dense materials.
Smart Images

Figure CN118360512B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric contact materials, and more specifically, relates to a preparation method of a high-density silver tin oxide electric contact material. Background Art
[0002] Environmentally friendly silver tin oxide (Ag-SnO2) electrical contact materials have broad application prospects in low-voltage electrical appliances such as relays, protectors, circuit breakers, and air switches. Their main function is to connect, conduct, and disconnect currents. Their performance has a direct impact on the reliability, stability, and even service life of electrical systems. So far, Ag-SnO2 electrical contact materials are mainly prepared by powder metallurgy and internal oxidation methods. Among them, powder metallurgy has obvious advantages. The composition of the prepared materials is precisely controllable, the organization is uniform, and it is suitable for mass production. The powder metallurgy process mainly includes mechanical mixing, pressing, sintering, and subsequent treatment. However, a certain number of tiny pores will remain inside the contact material prepared by powder metallurgy, which seriously affects the electrical contact performance of the material. In addition, SnO2 particles are also prone to agglomeration during the mechanical mixing process, and it is difficult to evenly disperse them inside the Ag matrix. Therefore, how to prepare highly dense Ag-SnO2 electrical contact materials by powder metallurgy is the main problem at present.
[0003] At present, advanced sintering technology and subsequent processing are mainly used to improve the density of Ag-SnO2 electrical contact materials. For example, hot pressing sintering and spark plasma sintering can improve the density of materials within a certain range. Sintering is carried out below the melting point of Ag, and the strength and density of the material are improved through solid-state diffusion between particles. However, during the molding process of the mixed powder under a certain pressure, the Ag particles with good plasticity combine with the hard SnO2 particles to form a blank, which will seal a small amount of gas inside and form isolated closed pores. Although the powder volume shrinks, the porosity and pore volume decrease during the sintering process, some enclosed gases are difficult to be completely discharged. The spark plasma sintering process can be performed without a pressing molding process, but due to the fast heating rate and short sintering time, some gases will remain inside the material, and even local melting will occur. Therefore, how to further improve the density of powder metallurgy products is still a current problem. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-density silver tin oxide electrical contact material, aiming to solve the problem of low density of existing powder metallurgy products.
[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a high-density silver tin oxide electrical contact material, comprising the following steps:
[0006] S01: Ag powder, SnO2 powder and CuO powder are mixed and ball-milled, and then pressed into a blank;
[0007] S02: Sintering the blank under high vacuum and high temperature at a temperature of 700°C-850°C to cause a thermal decomposition reaction of CuO;
[0008] S03: placing the sintered blank into a high temperature resistant mold, performing high temperature re-pressing and holding the pressure under high vacuum conditions, wherein the temperature range of the high temperature re-pressing is 700-800°C, the pressure range is 100-200MPa, and the holding time is 5-20 minutes;
[0009] S04: Release the pressure and cool down the furnace, and finally obtain a high-density Ag-SnO2 electrical contact material containing Cu2O additive.
[0010] In a possible implementation, in step S01, the mass percentages of Ag powder, SnO2 powder and CuO powder are: 76-91.5Ag powder, 8-20SnO2 powder, 0.5-4CuO powder.
[0011] In a possible implementation, in step S01, the mixed powder is subjected to low-energy ball milling using a ball mill, with a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm.
[0012] In a possible implementation, after the pellets are separated, they are annealed in a nitrogen environment at a temperature of 450° C. for 1 hour.
[0013] In a possible implementation, in step S01, the mixed powder is pressed into a cylinder in a steel film at a pressure of 600 MPa.
[0014] In a possible implementation, in step S02, the blank is placed in a vacuum furnace for sintering.
[0015] In a possible implementation, the vacuum degree of the vacuum furnace is 10 -3 Pa.
[0016] In a possible implementation, the high temperature resistant mold is made of stainless steel.
[0017] The scheme shown in the embodiment of the present application is compared with the prior art. The present invention provides a method for preparing a high-density silver tin oxide electrical contact material. First, Ag powder, SnO2 powder and CuO powder are pressed into a blank, and then high-temperature sintering is performed under a high vacuum environment. The sintered blank is placed in a high-temperature resistant mold, and high-temperature re-pressing is performed under high vacuum conditions and the pressure is maintained for a period of time. CuO in the blank is located in the closed pores. When CuO is sintered at high temperature under high vacuum conditions, a thermal decomposition reaction will occur. The chemical equation of the thermal decomposition reaction is 4CuO=2Cu2O+O2↑. With the expansion and flow of the generated O2, the closed pores formed during the pressing process are connected, thereby eliminating the residual gas in the closed pores. Since the blank is in a high vacuum environment, it is beneficial to extract O2 from the closed pores, thereby promoting the decomposition of CuO below 800°C; at the same time, the thermal decomposition reaction of CuO can also increase the bonding strength of the interface between Ag and SnO2. The preparation method of the high-density silver tin oxide electrical contact material of the present application can effectively eliminate the residual pores inside the electrical contact material and improve the compactness of the electrical contact material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A process flow chart of a method for preparing a high-density silver tin oxide electrical contact material provided by an embodiment of the present invention;
[0020] Figure 2 The EBSD phase diagram of the Ag-SnO2 (CuO) material prepared in Example 1 of the present invention before and after high temperature re-pressing;
[0021] Figure 3 The physical properties of the Ag-SnO2 (Cu2O) materials prepared in Examples 2, 3 and 4 of the present invention after high temperature re-pressing;
[0022] Figure 4 The arcing energy variation diagram of the Ag-SnO2 (Cu2O) electrical contact material prepared in Examples 2, 3 and 4 of the present invention after being interrupted 10,000 times;
[0023] Figure 5 Surface morphology of the anode after arc erosion of the Ag-SnO2 (Cu2O) electrical contact material (c, d) and the material without additive (CuO) (a, b) prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0025] See also Figure 1 Now, a method for preparing a high-density silver tin oxide electrical contact material provided by the present invention is described. The method for preparing a high-density silver tin oxide electrical contact material comprises the following steps:
[0026] S01: Ag powder, SnO2 powder and CuO powder are mixed and ball-milled, and then pressed into a blank;
[0027] S02: Sintering the blank under high vacuum and high temperature at a temperature of 700°C-850°C to cause a thermal decomposition reaction of CuO;
[0028] S03: placing the sintered blank into a high temperature resistant mold, performing high temperature re-pressing and holding the pressure under high vacuum conditions, wherein the temperature range of the high temperature re-pressing is 700-800°C, the pressure range is 100-200MPa, and the holding time is 5-20 minutes;
[0029] S04: Release the pressure and cool down the furnace, and finally obtain a high-density Ag-SnO2 electrical contact material containing Cu2O additive.
[0030] The present embodiment provides a method for preparing a high-density silver tin oxide electrical contact material. Compared with the prior art, Ag powder, SnO2 powder and CuO powder are first pressed into a blank, and then high-temperature sintering is performed under a high vacuum environment. The sintered blank is then placed in a high-temperature resistant mold, and high-temperature re-pressing is performed under high vacuum conditions and the pressure is maintained for a period of time. CuO in the blank is located in the closed pores. When CuO is sintered at high temperature under high vacuum conditions, a thermal decomposition reaction will occur. The chemical equation of the thermal decomposition reaction is 4CuO=2Cu2O+O2↑. With the expansion and flow of the generated O2, the closed pores formed during the pressing process are connected, thereby removing the residual gas in the closed pores. Since the blank is in a high vacuum environment, it is beneficial to extract O2 from the closed pores, thereby promoting the decomposition of CuO below 800°C; at the same time, the thermal decomposition reaction of CuO can also increase the bonding strength of the interface between Ag and SnO2. The preparation method of the high-density silver tin oxide electrical contact material of the present application can effectively eliminate the residual pores inside the electrical contact material and improve the compactness of the electrical contact material.
[0031] The melting point of CuO is 1446°C, and the decomposition temperature is around 1000°C, which is higher than the melting point of the Ag base (960°C). In order to reduce the decomposition temperature of CuO, this patent adopts high vacuum sintering to decompose CuO below 800°C, thereby avoiding the melting of the Ag base.
[0032] In some embodiments, in step S01, the mass percentages of Ag powder, SnO2 powder and CuO powder are: 76-91.5Ag powder, 8-20SnO2 powder, 0.5-4CuO powder.
[0033] In some embodiments, in step S01, the mixed powder is subjected to low-energy ball milling using a ball mill, with a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm.
[0034] In some embodiments, after the pellets are separated, they are annealed in a nitrogen environment at a temperature of 450° C. for 1 hour.
[0035] In some embodiments, in step S01, the mixed powder is pressed into a cylinder in a steel film at a pressure of 600 MPa.
[0036] In some embodiments, in step S02, the blank is placed in a vacuum furnace for sintering.
[0037] In some embodiments, in step S03, the vacuum degree of the vacuum furnace is 10 -3 Pa.
[0038] In some embodiments, the high temperature resistant mold is made of stainless steel.
[0039] Embodiment 1
[0040] Ag powder and SnO2 powder are mechanically mixed in a mass ratio of 92:8, 1wt.% CuO powder is added, and low-energy ball milling is performed on a planetary ball mill, using zirconium dioxide as grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 400 rpm. After separation of the balls and materials, annealing is carried out in a nitrogen environment at a temperature of 450°C and an annealing time of 1h. The mixed powder is pressed into a cylinder at a pressure of 600MPa in a steel mold, and then sintered in a vacuum furnace at a sintering temperature of 720°C and a sintering time of 3h. The initially fired sample is placed in a high-temperature resistant mold (the high-temperature resistant mold is also located in the vacuum furnace), and high-temperature re-pressing is performed under high vacuum conditions. The vacuum degree in the vacuum furnace is 10 -3 When the temperature of high temperature re-pressing reaches 800℃, keep it warm for 10 minutes, then apply 200MPa pressure with a jack, release the pressure after keeping the pressure for 10 minutes, and cool down with the furnace. Finally, Ag-8% SnO2 (Cu2O) electrical contact material is obtained.
[0041] Embodiment 2
[0042] Ag powder and SnO2 powder are mechanically mixed in a mass ratio of 92:8, 1wt.% CuO powder is added, and low-energy ball milling is performed on a planetary wheel ball mill, using zirconium dioxide as grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 400 rpm. After separation of the balls and materials, annealing is carried out in a nitrogen environment at an annealing temperature of 450°C and an annealing time of 1h. The mixed powder is pressed into a cylinder at a pressure of 600MPa in a steel mold, and then sintered in a vacuum furnace at a sintering temperature of 800°C and a sintering time of 3h. The initially fired sample is placed in a high-temperature resistant mold (the high-temperature resistant mold is also located in the vacuum furnace), and high-temperature re-pressing is performed under high vacuum conditions. The vacuum degree in the vacuum furnace is 10 -3 When the temperature of high temperature re-pressing reaches 800℃, keep it warm for 10 minutes, then apply 100MPa pressure with a jack, release the pressure after keeping the pressure for 10 minutes, and cool down with the furnace. Finally, Ag-8% SnO2 (Cu2O) electrical contact material is obtained.
[0043] Embodiment 3
[0044] Ag powder and SnO2 powder are mechanically mixed in a mass ratio of 90:10, 1wt.% CuO powder is added, and low-energy ball milling is performed on a planetary ball mill, using zirconium dioxide as grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 400 rpm. After separation of the balls and materials, annealing is carried out in a nitrogen environment at an annealing temperature of 450°C and an annealing time of 1h. The mixed powder is pressed into a cylinder at a pressure of 600MPa in a steel mold, and then sintered in a vacuum furnace at a sintering temperature of 800°C and a sintering time of 3h. The initially fired sample is placed in a high-temperature resistant mold (the high-temperature resistant mold is also located in the vacuum furnace), and high-temperature re-pressing is performed under high vacuum conditions. The vacuum degree in the vacuum furnace is 10 -3 When the temperature of high temperature re-pressing reaches 700℃, keep it warm for 10 minutes, then apply 100MPa pressure with a jack, release the pressure after keeping the pressure for 10 minutes, and cool down with the furnace. Finally, Ag-10% SnO2 (Cu2O) electrical contact material is obtained.
[0045] Embodiment 4
[0046] Ag powder and SnO2 powder are mechanically mixed in a mass ratio of 80:20, 1wt.% CuO powder is added, and low-energy ball milling is performed on a planetary ball mill, using zirconium dioxide as grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 400 rpm. After separation of the balls and materials, annealing is carried out in a nitrogen environment at a temperature of 450°C and an annealing time of 1h. The mixed powder is pressed into a cylinder at a pressure of 600MPa in a steel mold, and then sintered in a vacuum furnace at a sintering temperature of 800°C and a sintering time of 3h. The initially fired sample is placed in a high-temperature resistant mold (the high-temperature resistant mold is also located in the vacuum furnace), and high-temperature re-pressing is performed under high vacuum conditions. The vacuum degree in the vacuum furnace is 10 -3When the temperature of high temperature re-pressing reaches 700℃, keep it warm for 10 minutes, then apply 100MPa pressure with a jack, release the pressure after keeping the pressure for 10 minutes, and cool down with the furnace. Finally, Ag-20% SnO2 (Cu2O) electrical contact material is obtained.
[0047] See also Figure 2 ,It can be seen from the figure that after high-temperature re-pressing, the added CuO is converted into Cu2O, and the distribution of SnO2 inside the material is more uniform.
[0048] See also Figure 3 As can be seen from the figure, the Ag-8% SnO2 (Cu2O) and Ag-10% SnO2 (Cu2O) electrical contact materials prepared under vacuum initial sintering and vacuum re-pressing conditions have the best physical properties, with densities of 99.95% and 99.94% respectively, achieving the preparation of fully dense materials, which is higher than commercial products. In addition, the electrical conductivity reaches 79.3% IACS and 73.9% IACS, which is close to the extreme theoretical limit of the material. In addition, the density of the sample initially sintered in a vacuum environment after high-temperature re-pressing is higher than that of the sample initially sintered in a nitrogen environment, indicating that under vacuum environment sintering, the decomposition of CuO can fully reduce the closed porosity inside the material.
[0049] See also Figure 4 When the content of SnO2 is 8% and 10% respectively, the arc energy changes very stably. When the content reaches 20%, the arc energy increases.
[0050] See also Figure 5 The highly dense Ag-SnO2 (Cu2O) material has fewer holes on its surface and no large pores are formed.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density silver tin oxide electrical contact material, characterized in that: The steps include: S01: Ag powder, SnO2 powder and CuO powder are mixed and ball-milled, and then pressed into a blank; S02: Sintering the blank under high vacuum and high temperature. The blank is placed in a vacuum furnace for sintering. The vacuum degree of the vacuum furnace is 10 -3 Pa, the sintering temperature is 700℃-850℃, which makes CuO undergo thermal decomposition reaction; S03: placing the sintered blank into a high temperature resistant mold, performing high temperature re-pressing and holding the pressure under high vacuum conditions, wherein the temperature range of the high temperature re-pressing is 700-800°C, the pressure range is 100-200MPa, and the holding time is 5-20 minutes; S04: releasing the pressure and cooling down the furnace, finally obtaining a highly dense Ag-SnO2 electrical contact material containing a Cu2O additive; In step S01, the mass percentages of Ag powder, SnO2 powder and CuO powder are: 76%-91.5% Ag powder, 8%-20% SnO2 powder, 0.5%-4% CuO powder; After the ball material is separated, it is annealed in a nitrogen environment at a temperature of 450°C and an annealing time of 1 hour.
2. The method for preparing a high-density silver tin oxide electrical contact material according to claim 1, characterized in that: In step S01, the mixed powder is subjected to low-energy ball milling using a ball mill, with a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm.
3. The method for preparing a high-density silver tin oxide electrical contact material according to claim 2, characterized in that: In step S01, the mixed powder is pressed into a cylinder in a steel film at a pressure of 600 MPa.
4. The method for preparing a high-density silver tin oxide electrical contact material according to claim 1, characterized in that: The high temperature resistant mould is made of stainless steel.